Applying Dedicatory Pantun of Separation in Oral Assessment as Blended Learning Outcome - Sew, Jyh Wee (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
The discussion on teaching Malay pantun by means of innovative pedagogy follows the lead towards progressive Malay language education. In sustaining the Malay pantun, a series of methodologies are proposed as techniques that can provide a basic understanding of the four-line pantun to foreign language students, thus achieving an outcome that is indicative of high-level thinking skills. The pedagogical approach in question enabled two non-native students of Malay as a Foreign Language at the National University of Singapore (NUS) to voluntarily produce a four-line pantun as part of an oral recording in online learning via Zoom. The students’ responses are considered as a blended learning outcome that merits a close study of teaching Malay as a foreign language. Deductively, we focus on a combination of pedagogy in a lecture on their skill to create pantun. There are three sets of teaching appropriated in the complementary lecture. Firstly, the teaching of various monkey names to the students in order to develop their fauna terms in the construction of foreshadow in pantun and to improve their command of Malay proper nouns. Secondly, the teaching of Malay onomatopoeia as an appropriate element in pantun coinage so as to evoke their awareness of the Malayness language instinct. Thirdly, using a video clip of social interaction that displays the alternating acts of pantun exchange in order to broaden their vision to the practice of reciprocal pantun chanting, which remains well appreciated by the Malay speakers. The network of language pedagogy highlighted in inculcating their skills of pantun coinage is recommended as an effective blended teaching method. Full text : PDF